Risks and Resources for Depressive Symptoms and Anxiety in Children and Adolescents During the COVID-19 Pandemic – Results of the Longitudinal COPSY Study - Güzelsoy, Neslihan; Ravens-Sieberer, Ulrike; Westenhöfer, Joachim; Devine, Janine; Erhart, Michael; Hölling, Heike; Kaman, Anne (Frontiers in Psychiatry, 2022)
Background: Mental health during the COVID-19 pandemic is of particularly high relevance. Especially for children and adolescents, the pandemic and its restrictions represent a significant burden. The present study aims to identify risks and resources for depressive symptoms and anxiety in children and adolescents during the pandemic in Germany. Methods: Self-reported data from the first wave of the longitudinal COPSY study were used to investigate risks and resources among n = 811 children and adolescents aged 11 to 17 years. Depressive symptoms and anxiety were measured at the first follow-up six months later. Multivariate linear regression analyses were performed to investigate the effects of risks and resources on depressive symptoms and anxiety. Results: Parental depressive symptoms predicted depressive symptoms and anxiety in children and adolescents six months later. Female gender was identified as a risk factor for anxiety during the pandemic. None of the potential resources were associated with depressive symptoms or anxiety at the follow-up. Conclusions: The findings provide evidence of risk factors for depressive symptoms and anxiety during the COVID-19 pandemic. Children and adolescents who face risk factors need to be identified early and monitored during the pandemic. Family-based intervention programs are needed to help vulnerable children and adolescents cope with the challenges of the pandemic.